1994
DOI: 10.1093/oxfordjournals.cje.a035279
|View full text |Cite
|
Sign up to set email alerts
|

The increase in death and disease under ‘katastroika’

Abstract: The author describes recent trends in mortality and morbidity in the successor states to the former Soviet Union. Separate consideration is given to mortality under late perestroika (1987-1991) and subsequent mortality trends. The author concludes that "the collapse of the USSR and the problems of the successor states have had severe adverse affects not only on macroeconomic indices but also on the mortality and morbidity of the population.... Since the collapse of the USSR, the mortality situation in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 5 publications
0
39
0
2
Order By: Relevance
“…The dramatic social, political and economic changes that have happened in Russia during the 1990s are well documented (Ellman 1994;Rose 2000;Shkolnikov et al 1998a;Walberg et al 1998). In 1992 and 1998 Russia experienced two serious economic crises accompanied with drop in personal income and rapid impoverishment (Gavrilova et al 2000;Shkolnikov et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dramatic social, political and economic changes that have happened in Russia during the 1990s are well documented (Ellman 1994;Rose 2000;Shkolnikov et al 1998a;Walberg et al 1998). In 1992 and 1998 Russia experienced two serious economic crises accompanied with drop in personal income and rapid impoverishment (Gavrilova et al 2000;Shkolnikov et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Russian mortality crisis received significant attention in the scientific literature (Brainerd and Cutler 2005;Ellman 1994;Gavrilova et al 1997;Notzon et al 1998;Shkolnikov et al 1995aShkolnikov et al , b, 1998aShkolnikov et al , 2004Tulchinsky and Varavikova 1996;Walberg et al 1998). These studies showed that diseases of the circulatory system and injuries were the major causes of death contributing to the decrease in life expectancy in Russia after 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Murders rose by a reported 42 per cent in 1992 and a further 60 per cent in the first half of 1993. Russia's murder rate for the first half of 1993 stood at 25/100,000 people placing it firmly in the category of 'high homicide' countries, with rates well above most other 'high homicide' countries such as Mexico (20/100,000) and Brazil (15/100,000) [Ellman, 1994].…”
Section: Russiamentioning
confidence: 97%
“…This, and the sharp rise in poverty were the factors that caused an 'explosion of morbidity' (Murray Feshbach, quoted in Ellman [1994]. In 1993 it was revealed that alarming increases were occurring in infectious diseases such as measles, whooping cough, tuberculosis, and syphilis (the rise from 1990 to 1993 was 142 per cent, 72 per cent, 34 per cent and 300 per cent Downloaded by [University of Alberta] at 14:14 11 March 2015 respectively) [Ellman, 1994]. Large rises were reported also in diphtheria, dysentery and typhoid.…”
Section: Russiamentioning
confidence: 99%
See 1 more Smart Citation